(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article is devoted to the analysis of effective cost management in the activities of a joint-stock company in the construction sector. Cost management involves the effective implementation of strategy, as well as ensuring resource availability and technological discipline to achieve the highest possible levels of quality, reliability, and performance at minimal total costs. To compete effectively, secure resources for growth and innovation, and generate profit, enterprises need to achieve the best possible return on every dollar spent. When combined with appropriate software and digital technologies, strategies aimed at economic efficiency can help companies make more strategic decisions, foster innovation, turn procurement into a value-creating center, and reduce operating costs while enhancing operational efficiency and profitability.